Pengaruh Lokasi, Kualitas Pelayanan, Promosi dan Harga Terhadap Keputusan Pembelian Pada Vaneca Cafe - Risma Aditya Setiawan (International Forum of Researchers and Lecturers, 2024)
In the modern era, competition in business and business has become very tight, especially in the cafe business, many cafes have emerged, one of which is in the Kediri area. Kediri City is a small city that has many cafe business people and is not far behind the existing cafes. in big cities, therefore cafe owners have to think hard to be able to innovate and determine the right marketing strategy. A business that people are very interested in is cafes because consumers almost every day visit cafes not only to enjoy a cup of coffee but there are also those who want to enjoy the facilities available. The intense competition in the cafe business that is currently emerging has resulted in a problem often faced by business people, the first of which is a lack of attention to marketing strategies.